Asymptomatic myocarditis during clozapine re-titration, in a patient who had previously been stable on clozapine for 10 years. (December 2014) - Smith, Leo T; Symons, Evan; Hare, James L; Hooper, Michelle; Fitzgerald, Paul B
Objective: We present a case of confirmed clozapine-induced myocarditis in a patient who was not naïve to the drug. Method: This patient, who had been stable on clozapine for 10 years, relapsed following self-cessation. Asymptomatic throughout inpatient re-titration, serum cardiac enzymes were nonetheless routinely taken. Results: Occult myocarditis was only discovered due to an elevated Troponin I, and was confirmed by cardiac imaging. Conclusions: Once thought to be the preserve of initial exposure to the medication, clozapine-induced myocarditis can occur at any re-titration point if the immunological milieu permits. We therefore recommend routine monitoring of serum cardiac enzymes with all patients undergoing titration of clozapine, regardless of whether they have previously been stable on the drug.